A Five‐Tier System for Improving the Categorization of Transplant Program Performance. (13th June 2017) - Wey, Andrew; Salkowski, Nicholas; Kasiske, Bertram L.; Israni, Ajay K.; Snyder, Jon J.
Abstract : Objective: To better inform health care consumers by better identifying differences in transplant program performance. Data Source: Adult kidney transplants performed in the United States, January 1, 2012–June 30, 2014. Study Design: In December 2016, the Scientific Registry of Transplant Recipients instituted a five‐tier system for reporting transplant program performance. We compare the differentiation of program performance and the simulated misclassification rate of the five‐tier system with the previous three‐tier system based on the 95 percent credible interval. Data Collection: Scientific Registry of Transplant Recipients database. Principal Findings: The five‐tier system improved differentiation and maintained a low misclassification rate of less than 22 percent for programs differing by two tiers. Conclusion: The five‐tier system will better inform health care consumers of transplant program performance.